2021
DOI: 10.1136/bmjopen-2021-049135
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals in COVID-19-intensive care units in Norway: preparedness and working conditions: a cohort study

Abstract: ObjectiveTo survey the healthcare professionals’ background and experiences from work with patients with COVID-19 in intensive care units (ICUs) during the first wave of the COVID-19 pandemic in Norway.DesignObservational cohort study.SettingCOVID-ICUs in 27 hospitals across Norway.ParticipantsHealthcare professionals (n=484): nurses (81%), medical doctors (9%) and leaders (10%), who responded to a secured, web-based questionnaire from 6 May 2020 to 15 July 2020.Primary and secondary measuresHealthcare profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 28 publications
1
30
0
10
Order By: Relevance
“…The baseline study questionnaire was a composite package of 181 questions divided into eight parts. A previously published paper presents the ICU-HCPs’ preparedness and working conditions [ 25 ]. For the present paper, to focus on psychological reactions and support measures, 69 items were relevant as shown in the Supplementary Material .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The baseline study questionnaire was a composite package of 181 questions divided into eight parts. A previously published paper presents the ICU-HCPs’ preparedness and working conditions [ 25 ]. For the present paper, to focus on psychological reactions and support measures, 69 items were relevant as shown in the Supplementary Material .…”
Section: Methodsmentioning
confidence: 99%
“…In a French study of critical care clinicians in 21 ICUs (n = 1058), six independent factors were associated with psychological reactions: fear of being infected; inability to rest; inability to care for family; struggling with difficult emotions; regret about the restrictions in visitation policies; and witnessing hasty end-of-life decisions [ 15 ]. Moreover, studies have shown an increase in psychological reactions in women [ 7 , 22 ], being a nurse [ 23 ], and worrying about self or family members being infected [ 7 , 16 , 24 , 25 ]. Other significant factors were anxiety with respect to the availability of personal protective equipment (PPE) [ 16 , 26 ], being responsible for other staff members, being asked to work outside one’s expertise area and not feeling supported in the work environment and team [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 16 , 17 However, frontline COVID-19 health professionals are older in high-income countries than in low-income countries, with studies from the United States and Norway, reporting a mean age of 44 years. 18 , 19 With the COVID-19 pandemic, many developed countries are concerned about the ageing workforce in general, and in the healthcare sector, in particular. 20 This could be explained by the population pyramid difference amongst low-, middle- and high-income countries.…”
Section: Discussionmentioning
confidence: 99%